2009
DOI: 10.1007/978-3-642-01973-9_14
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Calculation of the Structure and Electronic Properties of Cu n O n (n=1-4) Clusters

Abstract: Abstract. We have performed ab initio Monte Carlo simulated annealing simulations and density functional theory calculations to study the structures and stabilities of copper oxide clusters, CunOn (n=1-4). We determined the lowest energy structures of neutral, positive and negatively charged copper oxide clusters using the B3LYP/LANL2DZ model chemistry. The geometries are found to undergo a structural change from two-to three-dimensions when n = 4 in the neutral clusters. We have investigated the size dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…However, the most stable structures for Cu 4 O 4 + and Cu 5 O 5 + were found to be 3D structures containing an O−O bond, which were also previously obtained theoretically by another group. 22 For Cu 2 O 2 + , Ω calc of the 2D zigzag planar isomer (49.9 Å 2 ) was found to be in good agreement with Ω exp (50.2 ± 2.5 Å 2 ). As for Cu 3 O 3 + , Ω calc of the best-fitted structure (56.3 Å 2 ) or the most stable cyclic structure (56.9 Å 2 ) did not agree well with Ω exp (51.4 ± 2.3 Å 2 ) at the present calculation level.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…However, the most stable structures for Cu 4 O 4 + and Cu 5 O 5 + were found to be 3D structures containing an O−O bond, which were also previously obtained theoretically by another group. 22 For Cu 2 O 2 + , Ω calc of the 2D zigzag planar isomer (49.9 Å 2 ) was found to be in good agreement with Ω exp (50.2 ± 2.5 Å 2 ). As for Cu 3 O 3 + , Ω calc of the best-fitted structure (56.3 Å 2 ) or the most stable cyclic structure (56.9 Å 2 ) did not agree well with Ω exp (51.4 ± 2.3 Å 2 ) at the present calculation level.…”
Section: Resultsmentioning
confidence: 57%
“…Hall et al investigated copper oxide cluster cations, Cu n O n + (n = 1−8), and found that the clusters are planar up to n = 3. 22 Most of the previous studies involved structural assignments based on theoretical calculations, and there have been few experimental studies on stable stoichiometric composition and geometric structures; even those were combined with theoretical calculations. In the present study, stoichiometric compositions and size-dependent structures of copper oxide cluster cations have been investigated by ion mobility mass spectrometry (IMMS).…”
Section: Introductionmentioning
confidence: 99%
“…This value is higher than the theoretical value of 0.181 nm (ref. 64) obtained from density functional theory calculation using B3LYP/LANL2DZ and experimental value of 0.1704 nm (ref. 65) obtained for a single CuO molecule at 0 K. This discrepancy is unsurprising as single molecules are expected to have a different bond length than NPs or bulk systems.…”
Section: Resultsmentioning
confidence: 99%
“…If one considers also a typical Cu-O bond length of ca. 0.18 nm [40] the ethion particle can undoubtedly connect across two Cu (II) ions over the MOF channel. Accordingly, this work proves that 14C-ethion can significantly remove using Cu-BTC [41].…”
Section: Herbicides and Pesticides Removalmentioning
confidence: 99%